Answer:
6 and -4
Step-by-step explanation:
a + b = 2
a - b = 10
Solve:
from the first eq.
a = 2 - b
replacing this value in the second eq.
(2-b) - b = 10
2 - 2b = 10
-2b = 10 - 2
-2b = 8
b = 8/-2
b = -4
from the second eq.
a - b = 10
a - (-4) = 10
a + 4 = 10
a = 10 - 4
a = 6
Check:
from the first eq.
6 + (-4) = 2
6 - 4 = 2
If the line has a slope = 0, then it's a horizontal line
with the equation y = constant.
The line passes through (0, -3) → y= -3
<h3>Answer: y = -3</h3>
is a monomial (since it is all connected by multiplication) and since it is in the degree of 2, that makes it a quadratic.
-2 is a constant (since it doesn't have variables) and it is a monomial (since it is all connected by multiplication)
3x-9 is a binomial (since it has two terms, not connected by multiplication) and since it has x in the power of 1, that makes it a linear equation.
Finally,
-6x + 9 is a trinomial (since it has 3 terms connected by either addition or subtraction) and since the degree of the polynomial is 2, that makes it a quadratic.
Answer:
Step-by-step explanation:
Complement of the event